An appraisal analysis of judgment and appreciation in nam cao’s short stories - Võ Nguyễn Thùy Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis was done in an effort to investigate and analyze the languages of Judgment and Appreciation in the category of Attitude, one of the three subsystems of the Appraisal theory in Nam Cao’s short stories and the English translational equivalents. In order to conduct the study, the descriptive analysis with the combination of both qualitative and quantitative research methods was adopted on the basis of the theories of Appraisal and Functional Grammar. The data for the study was built up with 300 Vietnamese samples of expressions of Judgment and Appreciation and 300 English translational equivalents in such forms as words, phrases, clauses and sentences from seven short Vietnamese stories by Nam Cao and the English translational version by Nam Cao. The study examined the semantic features and grammatical realizations of Judgment and Appreciation-expressions recognized in seven short Vietnamese stories and the English equivalents. Semantically, in the light of Appraisal Theory, the study revealed that Judgment expressions were realized in five sub-types, namely Normality, Capacity, Tenacity, Veracity, and Propriety, while Appreciation ones were also seen in five sub-types including Impact-Reaction, Quality-Reaction, Balance-Composition, Complexity-Composition, and Valuation. In terms of grammatical realization, based on Functional Grammar, the study found that the languages of Judgment and Appreciation were grammatically realized via such grammatical forms as Noun phrases, Verb phrases, Adjective phrases and Adverbial phrases in the Clause as Message, Clause as Exchange and Clause as Representation in form of both explicit and implicit. On the basis of the findings, several implications and suggestions on comprehending, translating the language of Judgment and Appreciation as well as learning and teaching English through language of Judgment and Appreciation in particular and Appraisal language in general were put forward